Układy cen czterech zbóż jako efekt różnicowania się struktury produkcji i rynku zbożowego w Polsce Ludowej - Kędelski, Mieczysław (Wydział Prawa i Administracji UAM, 1970)
The author of the paper presents and analyses the price relation of four cereals in People's Poland against the functioning of corn market in the circumstances of its segmentary break and its variety growing in time and space. He uses internal price relations, and so exchangeable relations of two cereals in one of the segmentary markets, to show convergence of market incentives and production trends. He examines the four cereals supply preferences against mutual price relations of the same cereal in various sections of the corn market in this country, as well as against the links and similarities of relations occurring in this country and in foreign markets. The author comes to the conclusion that price relations of each of the cereals in the 25-years' period od People's Poland differred in stimulant and adjustment power. The research object considered in the abstract however, does not reflect all the real correlations and the influence determinants ruling price relations of the four cereals, because all the problems of interrelation with the complex agricultural market and the other ones had to be disregarded although they are essential directions of agricultural production and foodstuff consumption.
Price Relations of Four Cereals as an Effect of the Growing Variety in Production Structure and Com Market in People's Poland